Development of an anti‐BAG3 humanized antibody for treatment of pancreatic cancer. Issue 6 (17th May 2019) - Basile, Anna; De Marco, Margot; Festa, Michelina; Falco, Antonia; Iorio, Vittoria; Guerriero, Luana; Eletto, Daniela; Rea, Domenica; Arra, Claudio; Lamolinara, Alessia; Ballerini, Patrizia; Damiani, Verena; et al.
Abstract : We have previously shown that secreted BAG3 is a potential target for the treatment of pancreatic ductal adenocarcinoma and that pancreatic tumor growth and metastatic dissemination can be reduced by treatment with an anti‐BAG3 murine antibody. Here, we used complementarity‐determining region (CDR) grafting to generate a humanized version of the anti‐BAG3 antibody that may be further developed for possible clinical use. We show that the humanized anti‐BAG3 antibody, named BAG3‐H2L4, abrogates BAG3 binding to macrophages and subsequent release of IL‐6. Furthermore, it specifically localizes into tumor tissues and significantly inhibits the growth of Mia PaCa‐2 pancreatic cancer cell xenografts. We propose BAG3‐H2L4 antibody as a potential clinical candidate for BAG3‐targeted therapy in pancreatic cancer. Abstract : BAG3 protein secreted by pancreatic cancer cells favors tumor growth by recruiting macrophages and fibroblasts. Here, we developed a humanized anti‐BAG3 Ab that localizes into the tumor and is able to hamper tumor growth. BAG3‐H2L4 is the lead variant with potential to be further developed for clinical purposes.